1997
DOI: 10.1183/09031936.97.10051130
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of sparfloxacin and ciprofloxacin into alveolar macrophages, epithelial lining fluid, and polymorphonuclear leucocytes

Abstract: Sparfloxacin (SPX), a novel fluoroquinolone with a broad spectrum of antibacterial activity, has been shown, in vitro, to be more effective against common pulmonary pathogens, particularly Streptococcus pneumoniae, Mycoplasma pneumoniae and some intracellular organisms, than ciprofloxacin (CPX).The objective of this open, comparative, randomized study in two parallel groups was to assess the serum concentrations and penetration of SPX and CPX into alveolar macrophages (AMs), epithelial lining fluid (ELF), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…The calculated values of AUC last for LO and laninamivir in AM were 77 to 364 times higher than those for the drugs in ELF (Table 2). High-level accumulation in AM was also observed in several human BAL studies after the oral administration of antibiotics (3,5,8,18,22). The uptake mechanism of clarithromycin and azithromycin to AM was explored using cultured AM cells (NR8383 cells), and it was found that the uptake was partly reduced by ATP depletors (21).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The calculated values of AUC last for LO and laninamivir in AM were 77 to 364 times higher than those for the drugs in ELF (Table 2). High-level accumulation in AM was also observed in several human BAL studies after the oral administration of antibiotics (3,5,8,18,22). The uptake mechanism of clarithromycin and azithromycin to AM was explored using cultured AM cells (NR8383 cells), and it was found that the uptake was partly reduced by ATP depletors (21).…”
Section: Discussionmentioning
confidence: 98%
“…Drug concentrations in epithelial lining fluid (ELF) and alveolar macrophages (AM) obtained from BAL fluid have been evaluated in healthy volunteers (1,5,8,18) as well as lung transplant recipients (3,22) and critically ill patients (9) to consider the efficacy of drugs against respiratory pathogens and the appropriate dosage regimens for antiinfective drugs. Among the neuraminidase inhibitors, the concentration of zanamivir in ELF after intravenous (i.v.)…”
mentioning
confidence: 99%
“…Sunlight exposure is much easier to control when patients are hospitalized. No phototoxic reactions were observed in volunteer studies with spar¯oxacin [17,21,22], or in the pneumonia studies [19,20]. In these studies, the compliance of volunteers and patients was excellent in contrast to TB patients.…”
Section: Discussionmentioning
confidence: 76%
“…The elimination half-life (t1/2) is approximately 15±20 h which allows once daily administration. Spar¯oxacin diffuses well into tissues and respiratory tract secretion and concentrates within macrophages, where mycobacteria survive and multiply [12,17].…”
Section: Spar¯oxacinmentioning
confidence: 99%
“…We also aimed to elucidate the feature of ulifloxacin uptake in rat lung and human lung adenocarcinoma cells (Calu-3). Sparfloxacin 16) and levofloxacin 17) are the quinolones with high and low penetration into the ELF, respectively. Azithromycin is a macrolide which highly penetrates into the ELF.…”
mentioning
confidence: 99%